Germination seeds of millet genotypes under the influences of PEG 6000 solution on the 3d and 6th days - О. В. Горлачова; С. М. Горбачова; В. С. Лютенко; О. В. Анциферова (Plant Varieties Studying and Protection)
Purpose. To determine the drought resistance of five millet varieties (ʻOmriyaneʼ, ʻKharkivske 57ʼ, ʻKonstantinovskeʼ, ʻIR 5ʼ, ʻSlobozhanskeʼ) using PEG 6000 as osmotic stress.